Alzheimer's Disease - A Comprehensive Review - Kinga Woźniak; Monika Gardian-Baj; Magdalena Jung; Patryk Hedesz; Maximilian Jung; Aleksandra Żuk-Łapan; Aleksandra Doryń; Krystian Jędral; Aleksandra Włodarczyk; Alicja Szczerbiak; Justyna Popczyńska (Kazimierz Wielki University, 2024)
Introduction: Alzheimer's disease (AD) remains a pervasive and challenging neurodegenerative disorder with profound implications for individuals, families, and societies. As the most prevalent cause of dementia globally, AD's prevalence is set to rise significantly in the context of an aging population. This introductory section emphasizes the urgent need for a comprehensive understanding of the disease, encompassing both its molecular intricacies and the socio-economic burden. With age being the primary risk factor, recent research has delved into the complex interplay of genetic predisposition and environmental influences, reshaping our understanding of AD from a multifactorial perspective. Current State of Knowledge: Advancements in Alzheimer's research have led to a nuanced understanding of its pathology. Traditionally characterized by amyloid-beta plaques and tau tangles, recent insights from neuroimaging and biomarker studies have revealed the intricate nature of these pathologies and their roles in disease progression. Genetic studies, including genome-wide association analyses, have identified susceptibility loci, notably the APOE gene. Simultaneously, environmental factors, such as air pollution and lifestyle choices, are recognized contributors to AD risk. The therapeutic landscape has evolved, with ongoing investigations into anti-amyloid and anti-tau therapies, lifestyle interventions, and precision medicine approaches. The synthesis of these diverse findings highlights the dynamic nature of Alzheimer's research and its potential to shape future treatment modalities. Summary: In summary, this article provides a comprehensive overview of the current state of knowledge regarding Alzheimer's disease. From understanding its evolving pathology to exploring the interplay of genetic and environmental factors, the multifactorial nature of AD is underscored. The therapeutic landscape is actively advancing, presenting a hopeful outlook for future treatments.